2014
DOI: 10.1590/1807-1929/agriambi.v18n12p1241-1246
|View full text |Cite
|
Sign up to set email alerts
|

Estado nutricional e produção da pimenteira com uso de biofertilizantes líquidos

Abstract: Os biofertilizantes podem melhorar a sanidade das plantas e incrementar a produtividade das culturas, com baixo custo. Objetivou-se, com este trabalho, avaliar o estado nutricional e características relacionadas à produtividade do fruto de pimenteira em resposta à aplicação de biofertilizantes líquidos na variedade de pimenta Dedo de Moça (Capsicum baccatum var. pendulum L.). O trabalho foi realizado em campo, no município de Teresina, Piauí, Brasil, no período de dezembro de 2010 a setembro de 2011. O delinea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 12 publications
0
14
1
2
Order By: Relevance
“…These results differ from those obtained by Oliveira et al (2014), who analyzed the nutritional status and characteristics related to the yield of pepper fruits in response to the application of liquid biofertilizers and observed that, except for calcium contents, the evaluated nutrients were below the range considered as adequate for the crop. 2.…”
Section: Resultscontrasting
confidence: 99%
“…These results differ from those obtained by Oliveira et al (2014), who analyzed the nutritional status and characteristics related to the yield of pepper fruits in response to the application of liquid biofertilizers and observed that, except for calcium contents, the evaluated nutrients were below the range considered as adequate for the crop. 2.…”
Section: Resultscontrasting
confidence: 99%
“…The direct effect of the application of bovine manure biofertilizers in the soil is the increase in the availability of nutrients (Alves et al, 2009;Cavalcante et al, 2011a;Lemes et al, 2013;Oliveira et al, 2014), as a function of the soluble minerals (Tables 1, 2 in the organic input and by the direct action of the pathogen on its host (Santos, 1992;Marrocos et al, 2012;Shivlata & Satyanarayana, 2015).…”
Section: Applications and Edaphic Effects Of The Biofertilizermentioning
confidence: 99%
“…In fruit species, the application is performed via leaf spraying (Marini, 2008), soil (Mesquita et al, 2010;Silva et al, 2016a;Tullio et al, 2018), and also via fertigation (Santana et al, 2016). In vegetable crops, the application directly on the soil is predominant (Nileemas & Sreenivasa, 2011;Viana et al, 2013;Borges et al, 2014), as well as on the leaves (Oliveira et al, 2014). Cavalcante et al (2019) Biofertilizers in horticultural crops…”
Section: Nutritional State and Physiologymentioning
confidence: 99%
See 2 more Smart Citations